Optimal Utilization Of Alternative Energy Sources - Rosa, Duane J. (International Business & Economics Research Journal (IBER), 2009)
Many areas of the world today have access to alternative energy sources to meet their energy needs. A fundamental problem facing societies today is to determine the optimum utilization of energy sources. This paper analyzes the issues involving co-utilization of different types of energy production in Iceland. Formulating a dynamic social optimization problem, expressions are derived for optimal energy supply prices from each energy source. Based on the economic characteristics of the energy sources, an optimal solution is derived that involves both periods of specialization in a single energy source as well as periods of simultaneous co-utilization of available sources.